(untitled) (Bangladesh Journal of Botany, 2019)
Analysis on the accumulation of oridonin in different parts of Isodon rubescens was studied. The contents of oridonin in all parts of I. rubescens were analyzed with RP-HPLC. The results showed that the differences between the contents of oridonin in the different parts of I. rubescens are extremely significant. The content of oridonin in the leaf of I. rubescens is higher than that of other parts. The content of oridonin in the stem was close to that of leaf. The root of I. rubescens had lowest content of oridonin in the three portions. But the content of oridonin in the root obtained was 0.0811 mg/g. The root in long run should be utilized to avoid wasting the I. rubescens resources.